2004
DOI: 10.1111/j.0022-2445.2004.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience and Strengths of Low‐Income Families

Abstract: This study examines indicators of family strength among a random sample of low‐income households with children. The Family Strength Index assesses strength according to economic, problem‐solving, communication, family cohesion, and social support assets. Variations in family strength are explained according to parental status and level of employment. Logistic regression is used to examine the contribution of assets to family outcomes. Findings indicate that relationship assets such as communication, problem so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 23 publications
9
165
0
6
Order By: Relevance
“…Assets are an especially important economic resource. However, most family research has overemphasized income as the source of economic well-being or does not adequately measure assets (Mistry, Lowe, Benner, & Chien, 2008;Orthner, Jones-Sanpei, & Williamson, 2004). For example, Werner and Smith's (2001) seminal Kauai study focused on chronic poverty as measured by household income as the indicator of economic resources.…”
Section: The Family Adjustment and Adaptation Response (Faar) Modelmentioning
confidence: 99%
“…Assets are an especially important economic resource. However, most family research has overemphasized income as the source of economic well-being or does not adequately measure assets (Mistry, Lowe, Benner, & Chien, 2008;Orthner, Jones-Sanpei, & Williamson, 2004). For example, Werner and Smith's (2001) seminal Kauai study focused on chronic poverty as measured by household income as the indicator of economic resources.…”
Section: The Family Adjustment and Adaptation Response (Faar) Modelmentioning
confidence: 99%
“…Social support has been linked to a variety of positive outcomes, including adaptive coping, parental competence, and better psychological adjustment. Supportive relationships with family members and significant others are seen as particularly relevant for individuals with high levels of life stress and can be viewed as an important protective factor because support buffers persons from the otherwise adverse impact of negative experiences (Orthner, Jones-Sanpei, & Williamson, 2004;Wills, Blechman, & McNamara, 1996). It has been suggested that the perception of social support is an important element of one's appraisal of and subsequent coping with stress.…”
Section: Protective Factorsmentioning
confidence: 99%
“…According to Simon, Murphy, and Smith (2005), determination to overcome their difficulties makes them feel strengthened and more confident. Thus, children of poor but resilient families are capable of accomplishing both academic and social-psychological achievements despite the lack of economic resources in their homes (Orthner et al, 2004). This is supported by the finding of www.ccsenet.org/ies International Education Studies Vol.…”
Section: Introductionmentioning
confidence: 93%